In Vitro regeneration and rapid multiplication of two orchid varieties of Dendrobium bensoniae and Dendrobium aphyllum - Riva, Sahida Siraj (BRAC University, 2017)
A Dissertation Submitted in Partial Fulfillment of the Requirements’ for the Degree of Master of Science in Biotechnology 2016.